PENDIDIKAN DAN LAYANAN KHUSUS ANAK DENGAN GANGGUAN KECERDASAN ATAU MENTAL (TUNAGRAHITA) - Susi Susanti; Iftah Tsaqofah; Prihartini; Herry Setiyatna (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
This article aims to find out how special education and services for children with intelligence or mental disorders. Education is the right of every Indonesian citizen, this is also the right of children with special needs to obtain special education. The term tunagrahita is used to refer to children or people who have an intellectual below average or can also be called mental retardasi and accompanied by an inability to adapt behavior. In the learning process, tunagrahita children experience obstacles in education so that curriculum modifications are needed according to their special needs. Children with disabilities need special education services and guidance in supporting their learning needs. The method used in this research is a qualitative approach and the method used in this article is library research, which means it is a technique that involves a series of actions in collecting various information. The results of this research are that education for mentally retarded children must pay attention to principles such as the use of simple language, appropriate placement in the classroom, repetition of material, and correlation with daily life, as well as ongoing evaluation to assess their individual development and needs.